Akulturasi Buddhisme di Jawa: Integrasi Ajaran Buddha dan Budaya Lokal dalam Pembentukan Simbolik Sosial - Wiwin Tania; Tri Yatno (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the process of acculturation between Buddhism and local culture in Indonesia, particularly in the context of the formation of a unique and historically relevant Nusantara Buddhist identity. The focus of the study includes the integration of the Tri Pitaka teachings with local cultural values, practices, language, art, and rituals to create a form of religious practice that is adaptive and meaningful for the local community. The research method used is a descriptive qualitative approach, with data collection techniques through observations of religious practices, interviews with religious and community leaders, and literature studies of relevant texts, inscriptions, historical artifacts, and scientific works. Data were analyzed interpretively through reduction, thematic grouping, and narrative construction that connects field phenomena to historical, social, and cultural contexts. The results show that the acculturation of Buddhism in Java is harmonious and multidimensional. The integration of Buddhism with local culture is manifested in the adaptation of ritual language, temple relief sculptures, ritual traditions such as Javanese puja bhakti (prayer offerings) and slametan (celebration ceremonies), and practices of respect for parents that align with Buddhist teachings. The Buddhist identity of the Indonesian archipelago is created through a synthesis of universal Buddhist values ​​and local culture, strengthening social cohesion and serving as a means of moral education for a multicultural society. This research contributes to the understanding of religious and cultural acculturation and opens up space for further study of the dynamics of religious integration in Indonesia.